(untitled) (Journal of Biomedical Investigation, 2022)
Background of the study: Despite the well-known benefits of physical activity (PA) participation, college students rarely meet the recommended benchmarks. Aim of the study: This study was aimed to examine the relationships among PA participation, exercise self-efficacy and motivation among college students. Material and methods: This cross-sectional study involved a simple random sample of 244 (122 males and 132 females) university students from Nnamdi Azikiwe University, Nnewi Campus, Anambra State, Nigeria. PA, exercise self-efficacy, and exercise self-motivation were assessed using International Physical Activity Questionnaire-short form, Self-Efficacy for Exercise measure and exercise motivations inventory-version 2 respectively. Descriptive and inferential statistics of Spearman’s rank order correlation and Mann Whitney U tests were used to summarize and analyze data. Results: The mean age of the respondents was 23.12±0.2 years. More than half of the respondents were moderately active (63.3%), had moderate exercise self-efficacy (54.9%), and moderate exercise self-motivation (59.4%). PA and exercise self-motivation were significantly correlated (r=0.145; p=0.023), Also, exercise self-efficacy and exercise self-motivation were significantly correlated (r=0.282; p=0.001). Higher participation in strenuous exercise among the male participants (U=6909.5; p=0.040) was observed. Conclusions: Moderate PA was predominant among Nigerian University Students. PA involvement was linked to increased exercise self-motivation.